2007
DOI: 10.1016/j.virol.2007.01.022
|View full text |Cite
|
Sign up to set email alerts
|

A minimal uORF within the HIV-1 vpu leader allows efficient translation initiation at the downstream env AUG

Abstract: The HIV-1 Vpu and Env proteins are translated from 16 alternatively spliced bicistronic mRNA isoforms. Translation of HIV-1 mRNAs generally follows the ribosome scanning mechanism. However, by using subgenomic env expression vectors, we found that translation of glycoprotein from polycistronic mRNAs was inconsistent with leaky scanning. Instead a conserved minimal upstream open reading frame (uORF) consisting only of a start and stop codon that overlaps with the vpu start site, appears to augment access to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 45 publications
4
39
0
Order By: Relevance
“…We assume that these ribosomes can reinitiate scanning on the RevEnv mRNA toward the Env AUG. Similar regulatory scenarios have been described previously for HIV-1 Vpu and Env translation (1,35,38) (Fig. 8C) but also in other viruses and eukaryotes (34,40,44,50).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…We assume that these ribosomes can reinitiate scanning on the RevEnv mRNA toward the Env AUG. Similar regulatory scenarios have been described previously for HIV-1 Vpu and Env translation (1,35,38) (Fig. 8C) but also in other viruses and eukaryotes (34,40,44,50).…”
Section: Discussionsupporting
confidence: 86%
“…8C). Inactivation of this uAUG reduced Env expression, consistent with the idea that this uAUG augments access to the downstream Env ORF (35). Second, alternatively spliced HIV-1 RNAs with a 5= extension (SA4 in Fig.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Since our HIV-2 G-box mutation results in a weaker Kozak context for AUG1, leaky scanning at this initiation site could enhance the use of at least one of the downstream start codons. Several laboratories have shown that in HIV-1 the strength of upstream AUGs can influence initiation at downstream AUGs (Schwartz et al 1992;Anderson et al 2007;Krummheuer et al 2007). Mutation of a weak upstream HIV-1 rev Kozak sequence to a strong initiating sequence resulted in decreased leaky scanning and poor initiation at the downstream vpu AUG ).…”
Section: Discussionmentioning
confidence: 99%